Innovation in Engineering Mechanics Learning in Vocational High Schools: Preliminary Study of V-Lab Development - Niswah, Aisyah Khilawatun; Roemintoyo, R; Rejekiningsih, Triana (Universitas Muhammadiyah Surakarta, 2022)
As one of the basic subjects that are important to be mastered by students, Engineering Mechanics subject has the aim that vocational school students have competence in calculating the behavior (deflections and forces) of structures against loads acting on building structures. This study aims to identify the problems faced by students during the implementation of learning. The research method is a quantitative approach by adopting a survey model. The research subjects consisted of first grade students majoring in civil engineering at public vocational high school 2 Surakarta. The data collection technique used a questionnaire followed by the data collection instrument using a questionnaire, the questionnaire was distributed in the form of a google form whose results were analyzed in percentage terms to describe the identification results. The findings of this study indicate that students need a variety of learning methods, considering that so far learning activities have been dominated by lectures and presentation slides. As many as 58.33% of students stated that the Engineering Mechanics learning tends to contain material that is difficult to understand, in addition 50% 'agree' and 29.17% 'strongly agree' students agree that the learning process tends to be boring. A total of 62.50% of students stated 'strongly agree' and 37.50% 'agree' had a strong learning motivation to understand the material in the Engineering Mechanics subject. The results of the study show that if an innovation is needed to support learning activities, especially Engineering Mechanics learning so that learning becomes more dynamic and active so as not to give students a sense of boredom.